Paradigma Penelitian Kualitatif dan Filsafat Ilmu Pengetahuan dalam Konseling - Batubara, Juliana (STKIP Muhammadiyah Pringsewu, 2017)
Abstract:Â This article is a study to understand the paradigm and philosophical foundations of research in counseling and guidance. Research is believed to be one of the pillars of science development. Simply scientific research is a consequence of human curiosity. Philosophy is a parameter of ontology science, epistemology, axiology, rhetorical structure, and methodology discussed throughout the paradigm of positivism, postpositivism, constructivism-interpretivism, and perspective-criticism. In the sense of finding solutions, discovering new things, explaining phenomena - correlation - comparability, repositioning truth, finding critics - theories - assumptions, reductions of circumstances or conditions change with expectations. Counseling research is expected to be able to explain, reposition, critic, and find an investigative approach within the identified research paradigm. The research will continue from various paradigms. In research guidance and counseling is an activity that can prove the importance of counseling and guidance services.Keywords: philosophy, qualitative research, guidance, counseling, paradigm